Modulation of Biodistribution, Pharmacokinetics, and Photosensitivity with the Delivery Vehicle of a Bacteriochlorin Photosensitizer for Photodynamic Therapy. Issue 2 (27th December 2013) - Saavedra, Raquel; Rocha, Luis B.; Dąbrowski, Janusz M.; Arnaut, Luis G.
Abstract Intravenous (i.v.) formulations with various amounts of organic solvents [PEG400, propylene glycol (PG), cremophor EL (CrEL)] were used to deliver a fluorinated sulfonamide bacteriochlorin to mice, rats, and minipigs. Biodistribution studies in mice showed that a low‐content CrEL formulation combines high bioavailability with high tumor‐to‐muscle and tumor‐to‐skin ratios. This formulation was also the most successful in the photodynamic therapy of mice with subcutaneously implanted CT26 murine colon adenocarcinoma tumors. Pharmacokinetic studies in mice and minipigs revealed that with the same low CrEL formulation, the half‐life of the photosensitizer in the central compartment was longer in minipigs. Differences in biodistribution with the various formulations, and in pharmacokinetics between the two animal species with the same formulation, are attributed to the interaction of the formulations with low‐density lipoproteins (LDLs). Skin photosensitivity studies in rats showed that 30 min exposure of the skin to a solar simulator 7 days after i.v. administration of the fluorinated sulfonamide bacteriochlorin at 1 mg kg−1 did not elicit significant skin reactions.